Prevalence of chronic diseases and practice of physical activity among adults and elderly - doi: 10.5020/18061230.2012.p209 - Michele Marinho da Silveira; Adriano Pasqualotti; Eliane Lucia Colussi (Universidade de Fortaleza, 2012)
Objective: To evaluate correlation between the prevalence of chronic diseases, diabetes mellitus and hypertension, and physical activity. Methods: A cross-sectional study, regarding descriptive variables and association, in which took part 53 adult and elderly subjects attending computer workshops offered by the Regional Center of Studies and Activities for the Third Age, managed by University of Passo Fundo. To analyze association between outcome variables, Mann-Whitney U test and Fisher's exact test were used, for a significance level of p ≤ 0.05. Results: Practice of physical activity was high and presented little difference between the sexes. With respect to diseases, hypertension was prevalent in both sexes, whereas diabetes mellitus was more prevalent among males. Conclusions: The practice of regular physical activity is part of daily life for the subjects studied, but even so, chronic diseases occur, especially hypertension, for men and women, and diabetes mellitus, among men.